The Effect of Poster Education on Public Knowledge of BEYOND-USE DATES in Bekasi Regency - Alfianna, Wiwin; Lestari, Amelia Lestari; Syafirna Renyaan, Dewi; Vinatalia, Elisabeth; Amalia, Nabila (Rifa'Institute, 2024)
There are two terms related to the time of use of drugs, namely the expiration date (ED) which is determined by the manufacturer, and beyond use date (BUD) which refers to the period of time after the drug is prepared or the primary packaging is opened. Indonesian people tend to store drugs based on ED. Ensuring the safe use of medicines is the role of pharmaceutical personnel, including providing information related to BUD. This research aims to determine the influence of poster media on the level of public knowledge and determine the role of pharmaceutical staff in providing information related to BUD. The research method used was an experimental survey of 600 respondents, using validated questionnaires and poster, which was carried out in hospital pharmacies, clinics, primary health care centers and pharmacies in Kabupaten Bekasi. The research results showed a significant difference in the pre-test and post-test scores with the Asymp.Sig scores. 0.000, which means that there was an increase in the level of knowledge of respondents after conveying BUD information through poster media, and as many as 80.3% of respondents stated that they had never received information related to BUD from pharmacy personnel. The poster has proven effective in increasing public knowledge regarding BUD. The active role of pharmaceutical personnel needs to be increased to ensure the safety and effectiveness of drug use in the community.